2010
DOI: 10.1007/s10608-009-9287-1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Appraisals of Internal States in Bipolar I Disorder: A Multiple Control Group Study

Abstract: Thirty individuals with Bipolar I Disorder (16 individuals had relapsed within the last 2 years; 14 individuals had remained well over this period) were hypothesized to score higher on extreme positive and negative appraisals of internal state (HAPPI; Hypomanic Attitudes and Positive Predictions Inventory) than three control groups: remitted unipolar depression group (n = 22), and non-clinical controls with (n = 16) or without (n = 22) a history of hypomanic episodes. In partial support of the primary hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 44 publications
(76 reference statements)
5
42
1
Order By: Relevance
“…These results were consistent across extreme pessimistic and extreme optimistic attributions, suggesting that the tendency to make extreme attributions in general might be more important in understanding course of illness than the valence of the attributions themselves. These studies have been broadly consistent with theoretical work and empirical studies of BSDs that suggest that individuals with BSDs make extreme appraisals about the meaning of internal mood states (Jones et al, 2006; Kelly et al, 2011; Mansell et al, 2007, 2011), and that these appraisals are associated with increases in symptoms of mood elevation and depression (Dodd et al, 2011). Notably, although studies among samples with unipolar depression also have found that extreme dysfunctional attitudes predict a poorer course of depression (Beevers et al, 2003; Forand & DeRubeis, 2014; Petersen et al, 2007; Teasdale et al, 2001), no study to date has evaluated this question in BSDs.…”
supporting
confidence: 80%
“…These results were consistent across extreme pessimistic and extreme optimistic attributions, suggesting that the tendency to make extreme attributions in general might be more important in understanding course of illness than the valence of the attributions themselves. These studies have been broadly consistent with theoretical work and empirical studies of BSDs that suggest that individuals with BSDs make extreme appraisals about the meaning of internal mood states (Jones et al, 2006; Kelly et al, 2011; Mansell et al, 2007, 2011), and that these appraisals are associated with increases in symptoms of mood elevation and depression (Dodd et al, 2011). Notably, although studies among samples with unipolar depression also have found that extreme dysfunctional attitudes predict a poorer course of depression (Beevers et al, 2003; Forand & DeRubeis, 2014; Petersen et al, 2007; Teasdale et al, 2001), no study to date has evaluated this question in BSDs.…”
supporting
confidence: 80%
“…The Hypomanic and Positive Predictions Inventory (HAPPI; Mansell, 2006) was constructed to measure key appraisals of the model. The HAPPI has been shown to distinguish bipolar groups from non-clinical controls (Mansell, 2006;Mansell & Jones, 2006) and from people with remitted unipolar depression (Alatiq, Crane, Williams, & Goodwin, 2010;Mansell et al, 2011) and to prospectively predict symptoms of bipolar disorder over one month when controlling for clinical variables (Dodd, Mansell, Morrison, & Tai, 2011). The model is also consistent with experimental (Mansell & Lam, 2006) and qualitative studies of bipolar disorder.…”
Section: Introductionmentioning
confidence: 57%
“…Consistent with this hypothesis, individuals with bipolar disorder have been demonstrated to have high levels of extreme (conflicting positive and negative) appraisals of internal mood states compared to individuals with major depressive disorder and healthy controls (Kelly et al, 2011; Jones, Mansell & Waller, 2006; Mansell et al, 2011). Furthermore, these appraisals predicted increases in symptoms of mood elevation and depression (Dodd et al, 2011).…”
Section: Introductionmentioning
confidence: 85%